Diffuse intrinsic pontine glioma: molecular landscape and emerging therapeutic targets. Issue 6 (November 2019) - Aziz-Bose, Razina; Monje, Michelle
Abstract : Purpose of review: Diffuse intrinsic pontine glioma (DIPG) is a fatal childhood brainstem malignancy. Despite advances in understanding of the molecular underpinnings of the tumor in the past decade, the dismal prognosis of DIPG has thus far remained unchanged. This review seeks to highlight promising therapeutic targets within three arenas: DIPG cell-intrinsic vulnerabilities, immunotherapeutic approaches to tumor clearance, and microenvironmental dependencies that promote tumor growth. Recent findings: Promising therapeutic strategies from recent studies include epigenetic modifying agents such as histone deacetylase inhibitors, bromodomain and extra-terminal motif (BET) protein inhibitors, and CDK7 inhibitors. Tumor-specific immunotherapies are emerging. Key interactions between DIPG and normal brain cells are coming to light, and targeting critical microenvironmental mechanisms driving DIPG growth in the developing childhood brain represents a new direction for therapy. Summary: Several DIPG treatment strategies are being evaluated in early clinical trials. Ultimately, we suspect that a multifaceted therapeutic approach utilizing cell-intrinsic, microenvironmental, and immunotherapeutic targets will be necessary for eradicating DIPG.